A study on emotional intelligence towards employee's job performance in organization at Selangor State Development Corporation (PKNS) Shah Alam, Selangor / Aimi Athirah Mohammad Tahir - Mohammad Tahir, Aimi Athirah (Faculty of Business and Management, 2018)
This research study is conducted to determine and analysed the relationship between Emotional Intelligent (EI) and Employee's Job Performance in Malaysia. The measurement used for independent variables was completed through several elements of EI which consist of self-awareness, self-management, social awareness and relationship management towards this research dependent variable which is job performance. Thus, the organization that has been chosen to conduct this research study is at Selangor State Development Corporation (PKNS). The instrument used to collect data in this study by using questionnaire. The researcher distributes personally the questionnaire to 54 employees at Selangor State Development Corporation (PKNS). As for this research is 54 employees from different department where 10 respondents is selected for pilot test and only 44 respondents of the population was selected as the sampling size for the actual study. After collecting all the questionnaires, all the data has been analysed for research questions, research objectives and hypothesis. The random sampling technique is the sampling technique that has been used in this study. In addition for the result of the reliability in the actual study the Cronbach's Alpha which includes of self-awareness is (0.779), self-management is (0.528), social awareness IS (0.895), relationship management is (0.796) and job performance is (0.897).Total questionnaires given to the respondents and received from them are the same amount of 54 sets. The relationship has been discovered between EI and job performance show positive and significant relationship which is moderate and strong relationship. It can be conclude that employee's results shows high correlation for relationship management and job performance, most of employees in Selangor State Development Corporation (PKNS), Shah Alam, Selangor show they are result-oriented with a high drive to meet the objective and standards